Yeast Nat4 regulates DNA damage checkpoint signaling through its N-terminal acetyltransferase activity on histone H4. - Mamantia Constantinou; Evelina Charidemou; Izge Shanlitourk; Katerina Strati; Antonis Kirmizis (PLoS Genetics)
The DNA damage response (DDR) constitutes a vital cellular process that safeguards genome integrity. This biological process involves substantial alterations in chromatin structure, commonly orchestrated by epigenetic enzymes. Here, we show that the epigenetic modifier N-terminal acetyltransferase 4 (Nat4), known to acetylate the alpha-amino group of serine 1 on histones H4 and H2A, is implicated in the response to DNA damage in S. cerevisiae. Initially, we demonstrate that yeast cells lacking Nat4 have an increased sensitivity to DNA damage and accumulate more DNA breaks than wild-type cells. Accordingly, upon DNA damage, NAT4 gene expression is elevated, and the enzyme is specifically recruited at double-strand breaks. Delving deeper into its effects on the DNA damage signaling cascade, nat4-deleted cells exhibit lower levels of the damage-induced modification H2AS129ph (γH2A), accompanied by diminished binding of the checkpoint control protein Rad9 surrounding the double-strand break. Consistently, Mec1 kinase recruitment at double-strand breaks, critical for H2AS129ph deposition and Rad9 retention, is significantly impaired in nat4Δ cells. Consequently, Mec1-dependent phosphorylation of downstream effector kinase Rad53, indicative of DNA damage checkpoint activation, is reduced. Importantly, we found that the effects of Nat4 in regulating the checkpoint signaling cascade are mediated by its N-terminal acetyltransferase activity targeted specifically towards histone H4. Overall, this study points towards a novel functional link between histone N-terminal acetyltransferase Nat4 and the DDR, associating a new histone-modifying activity in the maintenance of genome integrity.